Online shopping attitude and purchase intention of Nepalese consumers: Moderated mediation of social media - Shrestha, Sajeeb Kumar (Journal of Nepalese Management Academia, 2023)
People’s perception of online shopping grows day by day and becomes an essential part of the urban lifestyle. This study attempts to measure Nepalese consumers’ online shopping attitudes and purchasing intention to this phase witnessing the social media moderation. The analysis uses a quantitative research-based descriptive and causal research design. To gather responses from sample respondents, structured questionnaires were used, and surveys were carried out. Two hundred cross-section data was gathered. For checking the psychometric and econometric components of the suggested causal model, partial least square structural equation modeling was used. Trust is important factor for purchase intention in online platform. The same case, product variety and country of origin did not support for purchase intention in online mode. Attitude successfully mediates product variety, country of origin and trust to online purchase intention. Moderated mediation is not possible for social media with attitude to online purchase intention. This research has led to the development of online marketing strategies for online shoppers in the virtual community.